Pengaruh Rasio Tingkat Pengembalian Ekuitas, Rasio Lancar dan Rasio Utang Atas Ekuitas Terhadap Harga Saham Perusahaan Properti &Real Estate yang Terdaftar di BEI 2019 – 2023 - Amanda Hastika; Zain Zainuddin; Nita Astuti (CV. Kalimasada Group, 2025)
This study examines the effect of return on equity ,current ratio, and debt-to-equity ratio on stock prices of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Driven by inconsistent results from previous studies and the unique dynamics of the property sector during and after the COVID-19 pandemic, this study provides empirical evidence to clarify these relationships. Using panel data regression with Eviews 13, this study applies the Chow, Hausman, and Lagrange Multiplier tests to determine the best model. The results indicate that the current ratio has a negative and significant effect on stock prices, while the return on equity and debt-to-equity ratio do not show a significant effect on stock prices. The adjusted R² value of 9.9% indicates that other factors outside the model also play an important role in determining stock prices. These findings contribute to signaling theory by highlighting profitability as a key driver of investor decisions, while liquidity constraints can reduce investor confidence in the property sector. This study offers insights for investors, managers, and policymakers in formulating strategies to improve company performance and market valuation.